MEDIA SOSIAL DAN BAHASA ARAB: STUDI EKSPLORATIF TENTANG PERILAKU BERBAHASA SISWA SMK MUHAMMADIYAH 1 WELERI DALAM KONTEKS PEMBELAJARAN BAHASA ARAB - Muhammad Iqbal Faizul Mustofa; Rahmat Setiawan (As-Sulthan Journal of Education, 2025)
The lack of understanding about how social media affects the language behavior of students at SMK Muhammadiyah 1 Weleri in the context of learning, necessitates research to explore this phenomenon and understand how social media can be utilized to improve students' language skills in Arabic. This study uses a qualitative research approach with a case study design. The results of this study indicate that students use Arabic on social media to communicate, share information, and express themselves in the context of Arabic language learning. The factors that influence students' language behavior in using Arabic on social media are educational background, language proficiency level, language motivation, social media influence, and environmental influence. This study recommends that Arabic language education should consider the use of social media as one of the strategies for Arabic language learning.